Enduring exploitative leaders at work: The buffering role of proactive personality on employee job strain - Saleh Bajaba; Abdulah Bajaba; Bryan Fuller (Organization Management Journal (OMJ), 2022)
Purpose - This paper aims to study followers' proactive personality (PP) as a personal resource in moderating the hindering impact of exploitative leadership (EL) on followers' job strain (JS). Design/methodology/approach - Self-report data on EL, JS and PP were obtained from 113 working students in the USA, and a cross-sectional design was used. The data was analyzed using SPSS 27 through hierarchal multiple regression and the PROCESS macro. Findings - The findings support the buffering role of PP on the hindering impact of EL on JS, such that followers with higher PP tend to buffer the positive relationship between EL and followers' JS. Practical implications - This study recommends practitioners to hire proactive individuals and/or enable existing employees to engage in proactivity in the presence of exploitative leaders to better cope with their self-serving behaviors. Originality/value - Using the conservation of resources (COR) theory, this study is the first to use PP as a personal resource that protects against and mitigates the negative impact of EL.
Keywords: 650; Proactive personality; Conservation of resources theory; Job strain; Destructive leadership; Exploitative leadership